Kontribusi Motivasi Kerja dan Iklim Sekolah terhadap Kinerja Guru Agama Islam SMA Negeri di Kota Padang - Nur Adilah; Slamet Riyadi; Suwardi Suwardi (Journal on Education, 2023)
Based on the observations, it was found many teachers do not preparing a teaching device. Even some of them, teaching in the classroom without the use of RPP. Presumably the teacher's performance is still low in carrying out their duties. Lack of teacher performance allegedly due to low motivation of teachers and the less conducives’school climate.This study aims to reveal how big the contribution of Teachers’Work Motivation and school climate on the performance of Religion teachers of Senior High School in the district of Padang There were three hypotheses proposed in this research that teachers' motivation contribute to the performance of teachers, school climate contributes to teacher performance, teacher motivation and school climate contribute to the performance of teachers. Research method used was a quantitative correlational study with a population of primary school teachers in the district of Padang. State as much as 143 and the sample was taken as many as 97 people using Proportional stratified random sampling technique, taking into account years of service and educational strata. The instrument used was a tested questionnaire on its reliability and validity using SPSS version 16. The data was then analyzed using correlation and regression techniques. The results showed that the hypothesis were empirically acceptable. These findings can be concluded that the motivation of teachers and school climate are two factors that contribute to teacher performance. Therefore it is expected that the relevant parties to consider both factors that may increase teacher’s performance.